MINAT SISWA MAJJHIMA SEKHA MENGIKUTI KEGIATAN SEKOLAH MINGGU BUDDHA DI WIHARA DHAMMA PUTRA - Wardani, Mudita; Widiyono, Widiyono; Sukodoyo, Sukodoyo (Syailendra Buddhist College / Sekolah Tinggi Agama Buddha (STAB) Syailendra, 2021)
This study aims to find out, to provide recommendations, and to give suggestion about the interest of Majjhima Sekha students in participating the Buddhist Sunday School activities at Dhamma Putra Monastery. The research used qualitative descriptive methods. The research data was collected by interviews, observations, and documentations. The data was tested for its validity by observing, triangulating, and member checking. The Data analysis was based on the Miles & Huberman model which consisted of data collection, data reduction, data presentation, drawing conclusions, and verification. The results of this study indicate that there are two forms of Majjhima Sekha students' interest in participating Buddhist Sunday School. The Interest of participating Buddhist Sunday School activities caused be internal factors of the monastery, and external factors. The Internal factors that encourage are feeling happy without coercion. The External factors include peers, teachers, learning materials, and parents. The impact of interest in participating the Buddhist Sunday School is the increasing faith in Tri Ratna, the knowledge of Buddhism, and general knowledge, as well as the increasing self confidence. Futhermore, the impact obtained by Majjhima Sekha students in Buddhist is included in the four psychic powers (iddhipada) namely chanda, viriya, citta, and vimaṁsā.